2013
DOI: 10.1038/leu.2013.178
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric detection of dyserythropoiesis: a sensitive and powerful diagnostic tool for myelodysplastic syndromes

Abstract: Several groups have published flow cytometry scores useful for the diagnosis or prognosis of myelodysplastic syndromes (MDS), mainly based on the detection of immunophenotypic abnormalities in the maturation of granulocytic/monocytic and lymphoid lineages. As anemia is the most frequent symptom of early MDS, the aim of this study was to identify markers of dyserythropoiesis relevant for the diagnosis of MDS analyzed by selecting erythroblasts in a whole no-lysis bone marrow strategy by using a nuclear dye. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
109
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 20 publications
(19 reference statements)
16
109
1
Order By: Relevance
“…29 They demonstrated that FC correlated well with cytomorphology, albeit at a lower sensitivity (low/int-1 risk MDS, 64% vs. 84%, respectively); controls showed 11% and 10% of dysplasia by FC and cytomorphology, respectively. The findings presented herein confirmed results from a recent study 28 that reported a significant increase in CD71 CV and CD36 CV to be highly suggestive for MDS. Yet, discrimination between MDS and controls based on CV values was less clear in the current dataset.…”
supporting
confidence: 92%
“…29 They demonstrated that FC correlated well with cytomorphology, albeit at a lower sensitivity (low/int-1 risk MDS, 64% vs. 84%, respectively); controls showed 11% and 10% of dysplasia by FC and cytomorphology, respectively. The findings presented herein confirmed results from a recent study 28 that reported a significant increase in CD71 CV and CD36 CV to be highly suggestive for MDS. Yet, discrimination between MDS and controls based on CV values was less clear in the current dataset.…”
supporting
confidence: 92%
“…These results support the findings of Mathis et al, who tested the addition of erythroid evaluation by FC in nonlysed samples (RED score) to the diagnostic score. 22 The combination was analyzed in a cohort of 101 patients (83 MDS patients and only 18 controls) and resulted in a sensitivity and specificity of 88% and 89%, respectively. The RED score and the erythroid score described by the IMDSflow both comprised evaluation of CD36 CV and CD71 CV.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] The IMDS-flow group recently proposed guidelines for erythroid evaluation, advising the evaluation of CD36 coefficient of variation (CV), CD71 CV and mean fluorescence intensity (MFI), and percentage of progenitors (CD117 positive within CD45 negativediminished cell fraction) within the erythroid compartment. Sensitivity and specificity of this marker combination for the detection of MDS-associated erythroid aberrancies were 35% and 90%, respectively.…”
mentioning
confidence: 99%
“…The exact meaning of this heterogeneous expression is unclear, but flow cytometric abnormalities in CD71 and/or CD36 expression on immature erythroid cells are specific and recurrent findings in adult MDS patients. 8,10,11,[38][39][40] Flow cytometric evaluation of megakaryopoieis still has its limitations, but it was recently shown that abnormalities detected in peripheral blood platelets by flow cytometry are of diagnostic significance in adult MDS. 41 Future studies will be needed to reveal whether immunophenotyping of platelets and/or megakaryocytes can be of additional value in distinguishing RCC from (v)SAA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric immunophenotyping is a valuable addition to morphology in the diagnosis of MDS in adults. 7 Abnormalities detected by flow cytometry in myelomonocytic, erythroid and/or myeloid blast cells [8][9][10][11][12][13][14][15][16][17] can be of diagnostic and prognostic relevance in adult MDS. [18][19][20] In pediatric MDS, only a limited number of flow cytometric immunophenotyping studies have been reported.…”
Section: Introductionmentioning
confidence: 99%